Income Tax and Its Influence on Work Motivation: A Human Resource Management Perspective - Doni Saputra (Golden Ratio of Taxation Studies, 2024)
This research explores the intricate relationship between income tax policies and work motivation within organizational contexts. The study aims to empirically examine how income tax influences work motivation and to provide evidence-based recommendations for enhancing organizational policies and practices. Adopting a quantitative descriptive research design, data were collected through surveys or structured interviews from a diverse sample of employees across different industries. The analysis revealed that the tax burden and disposable income significantly impact employees' financial incentives and disincentives for work. Moreover, perceptions of tax fairness and distributive justice play a crucial role in shaping employees' attitudes toward work and organizational commitment. The findings underscore the need for organizations to consider the psychological and behavioral responses of employees to income tax policies and to develop strategies to mitigate negative impacts on work motivation. Key recommendations include fostering trust between taxpayers and tax authorities, promoting perceptions of fairness in tax policies, and creating a supportive organizational environment. This study contributes to advancing knowledge in both academic and practical realms, facilitating informed decision-making for organizational leaders and policymakers.